Associations between childbirth, gang exposure and substance use among young women in Cape Town, South Africa - Browne, F.A.; Carney, T.; Myers, Bronwyn; Bonner, C.P.; Wechsberg, W.M. (2024)
The prevalence and influence of gangs on adolescents and young adults remain a concern in Western Cape, South Africa—particularly as they have one of the largest gang presence. While less attention has been focused on young women, there is a need to elucidate the relationship between gang exposure and health behaviors, such substance use, in addition to understanding whether becoming a caregiver impacts this relationship. This study uses baseline data from 496 participants enrolled in a NIDA-funded R01 trial that recruited young women aged 16 to 19 who were out of school and reported recent alcohol or other drug use and sexual risk behavior. At enrollment, a risk behavior survey was administered, and urine drug screening was conducted. Multivariable logistic regression analyses were conducted to examine baseline associations between childbirth, a gang exposure index based on eight items, and positive drug screens of the most prevalent drugs in the Western Cape (marijuana, methaqualone, and methamphetamine). At enrollment, approximately 39% of the sample had a positive urine screen for marijuana, 17% for methaqualone, and 11% for methamphetamine. Additionally, 28% had ever given birth. While only 6% reported ever being a member of a gang, most reported exposure to gangs through their physical and social environments. For all three drugs, gang exposure was associated with statistically significantly higher odds of a positive screen. Every one-point increase in the gang exposure index was associated with a 31% increase in the odds of a positive marijuana screen (p <.001), a 26% increase for methaqualone (p = 0.005) and a 37% increase in the odds of a positive methamphetamine screen (p <.001). Ever given birth was associated with lower odds of marijuana use (adjusted odds ratio [AOR]: 0.63; 95% CI: 0.42–0.96), but it was not associated with methaqualone or methamphetamine use. The findings suggest that exposure to gangs through young women’s social and physical environment is positively associated with drug use. Childbirth was also protective for marijuana use, indicating there may be something unique about this type of drug, such as one’s ability to more easily stop use. Although very few young women reported gang membership, a majority reported some exposure, indicating the need to address how pervasive this exposure is and the potential risk.